For every child, vaccination (UNICEF Innocentí - Global Office of Research and Foresight, 2023)
The publication focuses on the importance of vaccination of children on a global level and on healthcare planning. Intended for professional public.
State of the world's children ; 2023
Keywords: veřejné zdravotnictví; Global Health; Child Health; dítě; pediatrie; Vaccination; Child; zdravotnické plánování; očkovací programy; celosvětové zdraví; preventivní medicína; vakcinace; Immunization Programs; Health Planning; zdraví dítěte